Recent advances of rodent models for alcoholic liver disease in evaluating healthy effects of food bioactive ingredients - Xiaoting Yu; Xuedi Zhang; Lijuan Zhang; Haitao Wang; Mingqian Tan (Food Science and Human Wellness)
The development of rodent models that accurately reflect the pathogenesis of alcoholic liver disease (ALD) in humans is crucial for evaluating the nutritional intervention of food bioactive ingredients in ALD. Although various models have been employed to establish ALD models over the past few decades, most successful cases are associated with high mortality rates, operational difficulties, and incompatibility formation mechanism compared to human ALD. However, the ALD models established by oral administration that simulate human drinking behavior often fail to induce significant liver damage. Therefore, it is imperative to explore simple and effective modes of oral administration for establishing ALD models consistent with the pathophysiological process of human ALD. Herein, we summarized the pathogenesis of ALD and discussed several issues related to construct ALD models with rodents (mainly mice and rats) by oral administration, including animal selection, animal feeding, alcohol intervention, and evaluation criteria. The purpose of this review is to provide a standardized and efficient formula for ALD modeling, so as to facilitate efficacy evaluation and mechanism analysis of food bioactive ingredients in ALD.